ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN LOMBOK TENGAH - Kurniawati Kurniawati; Sahar Sahar (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2022)
The study aims to describe the extent of effectiveness and how much a rwstaurant tax contributes to the region in Lombok central district from 2016 to 2020, and to find out what factors affect the effectiveness and contribution of the restaurant tax on the native income of Lombok central district. The type of descriptive research with a quantitative approach by using the established effectiveness and contribution formulas based on the effectiveness criteria table and contribution table. Data retrieved from Bappeda office Lombok central distict which is the original income recaip for the central Lombok county area. The effectiviness of restaurant tax revenues against the groth of native incomes in the middle of Lombok county budget year 2016 to 2020 is fluctuating and fit in very effective criteria where at each year there is a percentage rate of restaurant tax effectiveness the is substantial and exceeds established targets. The condition suggests that the ragion’s central government performance has hit its target or target very well. Whereas the contribution of restaurant tax tevenues to the growth of investment in the region in the middleof the year from 2016 through 2020 falls ata rate less than the year bellow 15,30% a year, although overall the contribution to restaurant tax revenues is fluctuating, the restaurant tax contribution are still far from the designated target.